Investigating the Precise Localization of the Grasping Action in the Mid-Cingulate Cortex and Future Directions - Rahman, Zebunnessa; Murray, Nicholas W. G.; Sala-Padró, Jacint; Bartley, Melissa; Dexter, Mark; Fung, Victor S. C.; Mahant, Neil; Bleasel, Andrew Fabian; Wong, Chong H. (Frontiers in Human Neuroscience, 2022)
Objective: To prospectively study the cingulate cortex for the localization and role of the grasping action in humans during electrical stimulation of depth electrodes. Methods: All patients (n=23) with intractable focal epilepsy and a depth electrode stereotactically placed in the cingulate cortex, as part of their pre-surgical epilepsy evaluation from 2015 to 2017, were included. Cortical stimulation was performed and examined for grasping actions. Post-implantation volumetric T1 MRIs were co-registered to determine exact electrode position. Results: Five patients (Male: Female 4:1; median age 31) exhibited contralateral grasping actions during electrical stimulation. All patients had electrodes implanted in the ventral bank of the right cingulate sulcus adjacent to the vertical anterior commissure (VAC) line. Stimulation of other electrodes in adjacent regions did not elicit grasping. Conclusions: Grasping action elicited from a localized region in the mid cingulate cortex directly supports the concept of the cingulate cortex being crucially involved in the grasping network. This opens an opportunity to explore this region with deep brain stimulation as a motor neuromodulation target for treatment in specific movement disorders or neurorehabilitation.